2014
DOI: 10.5897/ajb2013.13414
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of humic acids production by Trichoderma viride and Trichoderma reesei using the submerged fermentation of oil palm empty fruit bunch

Abstract: The remarkable properties of humic acids have generated a broad spectrum of applications in pharmaceutical, cosmetic and agricultural fields, and encouraged fermentation studies focusing on humic acids production. This work compares the humic acids production of Trichoderma (viride and reesei) species using empty fruit bunch as the substrate during submerged fermentation. The performance of each species was compared by examining spore production in oat medium, and the significant medium components and fermenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Although similar proportions exist among the components, the lignocellulosic content was higher in Type 1 EFBs. Motta and Santana (2014) found in their studies with EFBs proportions of 12% lignin, 27% cellulose and 39% hemicellulose. Therefore, it is possible to affirm that the values found in the present study were within the range presented in the literature, emphasizing that the variation in the lignocellulosic composition often depends on the soil and the region the EFBs come from.…”
Section: Lignocellulosic Characterization Of Efbsmentioning
confidence: 90%
See 2 more Smart Citations
“…Although similar proportions exist among the components, the lignocellulosic content was higher in Type 1 EFBs. Motta and Santana (2014) found in their studies with EFBs proportions of 12% lignin, 27% cellulose and 39% hemicellulose. Therefore, it is possible to affirm that the values found in the present study were within the range presented in the literature, emphasizing that the variation in the lignocellulosic composition often depends on the soil and the region the EFBs come from.…”
Section: Lignocellulosic Characterization Of Efbsmentioning
confidence: 90%
“…According to the literature, the use of EFBs in fermentation to obtain humic acids has already been studied (Motta and Santana, 2014). The results showed that EFBs are by-products with good potential for the production of humic acids using Trichoderma reesei, both in submerged fermentation and in solid state fermentation.…”
Section: Characterization Of Residual Lipids In Efbsmentioning
confidence: 99%
See 1 more Smart Citation